The views of children and young people on the use of silk garments for the treatment of eczema: a nested qualitative study within the CLOTHES randomised controlled trial - Wake, E.V.; Batchelor, Jonathan M.; Lawton, Sandra; Thomas, K.S.; Harrison, Eleanor F.; Cowdell, Fiona (Wiley, 2018)
Background: Many children suffer with skin diseases, but to date, most dermatological research has been done ‘on’ rather than ‘with’ children; in this study we actively sought the experiences of children and young people. Atopic eczema (AE) is a chronic, itchy, inflammatory skin condition that affects around 20% of children and can impact on health and wellbeing for children and their families. The role of specialist clothing in the management of AE is poorly understood.